Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1017/s0007114511001267
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast thylakoids reduce glucose uptake and decrease intestinal macromolecular permeability

Abstract: Thylakoid membranes, derived from chloroplasts, have previously been shown to retard fat digestion and lower blood glucose levels after oral intake. The purpose of the present study was to investigate the effect of thylakoid membranes on the passage of methyl-glucose, dextran and ovalbumin over rat intestine in vitro using Ussing chambers. The results show that thylakoids retard the passage of each of the test molecules in a dose-dependent way. The thylakoids appear to be attached on the mucosal surface and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
(52 reference statements)
2
31
0
Order By: Relevance
“…A decreased passage of glucose during the experimental period of 10 d would theoretically result in a lower secretion of insulin, resulting in higher insulin sensitivity. It has previously been reported that thylakoids, in a dose-dependent way, decrease the in vitro uptake of methyl-glucose over the rat intestinal wall ( 16 ) . The reason for this decrease could be either an indirect cause of a steric hindrance formed by thylakoids binding to the mucosa of the intestine, or less likely, a direct cause of thylakoids binding to glucose molecules ( 16 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A decreased passage of glucose during the experimental period of 10 d would theoretically result in a lower secretion of insulin, resulting in higher insulin sensitivity. It has previously been reported that thylakoids, in a dose-dependent way, decrease the in vitro uptake of methyl-glucose over the rat intestinal wall ( 16 ) . The reason for this decrease could be either an indirect cause of a steric hindrance formed by thylakoids binding to the mucosa of the intestine, or less likely, a direct cause of thylakoids binding to glucose molecules ( 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The experimental diet was composed of standard rat chow (R 36; Lantmännen) enriched with either only rapeseed oil (control diet) or a thylakoid–oil suspension (thylakoid diet). Thylakoid membranes were extracted and purified from fresh baby-spinach leaves as described before ( 14 , 16 ) . The thylakoid diet was prepared by mixing 4 g thylakoid powder (corresponding to 132 mg chlorophyll), 5 g rapeseed oil and 10 g water by using an Ultraturax mixer.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since thylakoids are biological membranes composed of proteins and lipids, digestive enzymes such as pepsin and trypsin degrade the thylakoid membranes after approximately four hours in vitro 16 . The degraded membranes eventually are detached from the oil-water interface and lipid digestion can continue without steatorrhea 17 .…”
Section: The Effect Of Thylakoid Isolates On Lipolysis When Included mentioning
confidence: 99%
“…While it is not clear how this works, chlorophyllin may interfere with gut glucose transporters or incretin signaling, e.g., acting as a glucagon-like peptide 1 (GLP-1) secretagogue. It is already known that chloroplast thylakoids reduce glucose uptake and suppress blood glucose levels [110,111]. Moreover, daily supplementation with green plant membranes for three months significantly reduced weight in overweight women via GLP-1 [112].…”
mentioning
confidence: 99%